Formulasi dan karakteristik nutrimat bar berbasis tepung kacang kedelai (glycine max. L) dan tepung kacang merah (phaseolus vulgaris. L) sebagai makanan pasien kemoterapi - Wiranata, I Gusti Agung Gede; Puspaningrum, Dylla Hanggaeni Dyah; Kusumawati, I Gusti Ayu Wita (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2017)
Background : The potency of soybeans and red beans as the source of antioxidant agents is very interesting to be developed as snack bar for chemotherapy patients. Nutrimat bar is made with addition of soybeans flour and red beans flour. The correct formulation will result in good characteristic of nutrimat bar. Methods : This research used Complete Random Design (RAL) with five types of treatment and three times of repetition. The formulations of soybeans flour and red beans flour being used were P1 (0:100); P2 (25:75); P3 (50:50); P4 (75:25); and P5 (100:0). Analysis to nutrimat bar was sensory characteristic analysis (taste, flavor, color and texture) and nutrient content analysis (protein, fat, carbohydrate and antioxidant). Data analysis used ANOVA with further testing of Smallest Real Difference (BNT). Results : The result of research shows that formulation with addition of soybeans flour and read beans flour has an effect towards characteristic of nutrimat bar quality being produced. Conclusion : The best nutrimat bar is made from formulation of P2 (soybeans flour of 25% and red beans flour of 75%) which producing characteristic of savory taste, non-rotten flavor, brown color and tender texture, with nutrient content value of protein at 12.75 g, fat at 4.71 g, carbohydrate at 35.36 g and antioxidant at 84.69 mg/L Galic Acid Equivalent Antioxidan Capacity (GAEAC).